Simulasi Kontrol Kecepatan Kendaraan Dengan Logika Fuzzy Metode Mamdani Pada Berbagai Keadaan - Sean Coonery Sumarta (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2013)
Traffic accident are the third killer in the world after HIV / AIDS and tuberculosis. Factors that cause accidents classified by elements of the transportation system itself are the road user, vehicle, road and environment. In this research apply fuzzy logic to control the vehicle speed limits by using Mamdani inference method. This research was carried out to control the driver so that not to accelerate the vehicle exceeds a predetermined speed limit based on surrounding circumstances. Circumstances which are used as variables: class, weather and distance between vehicles. The results of this research have been successfully made speed control vehicle simulation with fuzzy logic in matlab r2012a.